2020
DOI: 10.1101/2020.11.25.398586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of Small-Molecule Antagonists of the PWWP Domain of NSD2

Abstract: Increased activity of the lysine methyltrans-ferase NSD2 driven by translocation and activating mutations is associated with multiple myeloma and acute lymphoblastic leukemia, but no NSD2-targeting chemical probe has been reported to date. Here, we present the first antagonists that block the protein-protein interaction between the N-terminal PWWP domain of NSD2 and H3K36me2. Using virtual screening and experimental validation, we identified the small-molecule antagonist 3f, which binds to the NSD2-PWWP1 domai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Given that PHD and PWWP domains can read methylated amino acids and BDs can recognize acetylated lysine residues, it may be possible that ZMYND8's reader cassette recognizes combinatorial PTMs on the BRD4 ET domain, though those exact PTMs remain unclear and require further investigation. Recent advancements in chemical biology have demonstrated that the discrete reader pocket of the BD and PWWP domains are amenable to chemical perturbation (Clegg et al, 2019;Cochran et al, 2019;Filippakopoulos et al, 2010;de Freitas et al, 2020;Wimalasena et al, 2020). These findings highlight that therapeutic targeting of the reader modules in ZMYND8 can potentially be achieved by selective chemical probes.…”
Section: Discussionmentioning
confidence: 93%
“…Given that PHD and PWWP domains can read methylated amino acids and BDs can recognize acetylated lysine residues, it may be possible that ZMYND8's reader cassette recognizes combinatorial PTMs on the BRD4 ET domain, though those exact PTMs remain unclear and require further investigation. Recent advancements in chemical biology have demonstrated that the discrete reader pocket of the BD and PWWP domains are amenable to chemical perturbation (Clegg et al, 2019;Cochran et al, 2019;Filippakopoulos et al, 2010;de Freitas et al, 2020;Wimalasena et al, 2020). These findings highlight that therapeutic targeting of the reader modules in ZMYND8 can potentially be achieved by selective chemical probes.…”
Section: Discussionmentioning
confidence: 93%
“…We recently described the use of virtual screening, target class screening, and ligand-based scaffold hopping approaches to identify ligands of the NSD2 PWWP domains as starting points for further development 19 . This initial effort led to compound 3f which binds NSD2-PWWP1 with a K d of 3.4 ± 0.4 µM as determined by surface plasmon resonance (SPR).…”
Section: Discovery Of a Potent Ligand Targeting Nsd2-pwwp1mentioning
confidence: 99%
“…Specifically, we reported a potent chemical probe targeting the N-terminal PWWP domain of NSD3 that repressed MYC mRNA levels and reduced the proliferation of leukemia cell lines 18 . Additionally, we recently described the development of the first antagonist of NSD2-PWWP1 which binds with modest potency and abrogates H3K36me2 binding 19 . Therefore, we hypothesized that targeting the PWWP domain(s) of NSD2 with highly potent and selective chemical probes may be a strategy to modulate NSD2 engagement with chromatin, subcellular localization, and/or catalytic function.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations